Importované virové hepatitidy v Ceské republice - Dlhý, J; Benes, C (Klinicka mikrobiologie a infekcni lekarstvi, 2007)
OBJECTIVE: Through the analysis of notified viral hepatitis, trends in the occurrence of imported cases in the Czech Republic have been specified, the aim of which was to draw attention to the epidemiologically important aspects of travelling abroad. MATERIAL AND METHODS: In the software environment of Epi Info version 6.04d, nationwide databases of communicable diseases over the period of 1993-2005 were analysed. The period was defined with respect to the availability of necessary data in the Epidat information system for communicable disease reporting in the Czech Republic. RESULTS: During the years 1993-2005, 12,091 cases of communicable diseases were imported into the Czech Republic of which viral hepatitis accounted for 5.7 % (685). The rates by diagnosis were as follows: viral hepatitis A 61 %, acute viral hepatitis B 15 %, chronic viral hepatitis C 11 %, viral hepatitis E 5 %, acute viral hepatitis C 3 %, chronic viral hepatitis B 3 % and other cases of viral hepatitis 2 %. The rates by the "imported by" variable: Czech tourists 47.2 %, foreigners 32.8 %, Czech business travellers 20.0 %. The diseases were most commonly imported from the following countries: Ukraine 13 %, Slovakia 8 %, Southern Europe 6 %, Egypt 6 % and Russia 5 %. CONCLUSION: In the Czech Republic, communicable diseases are reported using the Epidat system. The Epidat database analysis focused on reported cases of imported viral hepatitis represents an important starting point for assessing health risks associated with travelling abroad.
Keywords: senioři; mladiství; Česká republika; Middle Aged; Adult; Czech Republic; dítě; Child; Travel; Child, Preschool; Hepatitis, Viral, Human; Humans; předškolní dítě; virová hepatitida u lidí; lidé středního věku; dospělí; Aged; Adolescent; cestování; lidé